Green banking; prospects & challenges in Bangladesh with highlights from Dhaka Bank Limited - Rahman, Md. Ziaur (Brac University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.